Pengaruh Edukasi dengan Media Linzi terhadap Sikap dan Kinerja Kader dalam Memantau Status Gizi Balita - Novita Ika Wardani; Listyaning Eko Martanti; Teguh Wahyudi (JURNAL KEBIDANAN, 2019)
Child nutrition problems can be handled from the start through the activation of the posyandu. The first screening was conducted at the posyandu by comparing body weight with age. Each cadre has a different attitude and performance in implementing posyandu. The use of assistive devices can influence the attitude and performance of cadres. The aim is to determine the effect of LINZI media on cadres' attitudes and performance. The sample used 25 treatment groups and 25 control groups. The attitude with paired t test showed that in the control group there was a difference between the pre test and post test p = 0.042 (p 0.05) and the treatment group p = 0.04 (P 0.05). The performance of paired t test showed that in the control group there was a difference between before and after p = 0.001 (p 0.05) and p = 0.000 (P 0.05) in the treatment group. There is the influence of LINZI media education on cadre attitudes with an average score of 33.08 treatment attitudes greater than controls 32.96. There is the influence of LINZI media education on the performance of cadres with an average performance score of 26.16 greater than the control 24.84. Cadres can use LINZI media for early screening of toddlers' nutritional status that is more interesting and easy to use.